Kedudukan Perempuan Dalam Kisah Mahabharata (Studi Terhadap Nilai-Nilai Feminisme Dalam Penokohan Dewi Drupadi) - Ni Putu Ida Sulistia; Untung Suhardi (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
This study discusses the values of feminism within the characterization Goddess Draupadi. The research is research study a text by a method of literature available. In analyzing the problem of used the concept of the women , Mahabharata , the value of feminism and the goddess Drupadi characterization using a technique and interpretation. This study tries to answer feminine values the goddess Drupadi in Mahabrata. Drupadi born from a fire ceremony and to become a tributary of the king Drupada. Drupadi married to Pandawa who won a competition. Suffering drupadi also began when she married into five men at once was humiliated and sent to the palace. Due to the game of craps, Drupadi also be a victim of a bet by her husband. For revenge and justice for what has done the Kurawa, Drupadi make war upon insult Kurawa done. The feminine values indicated in characterization Drupadi is sacrifice women, allegiance to the husband and gender equality. In addition, the role of equality and social shown Drupadi among other women as the mother, women as managers of religion and women in community life. While the women in general in Mahabrata namely women as a symbol of glory, the successor of ancestral tradition of esteem and honor women. Feminine values that are in the goddess Drupadi penokohan is a good thing for role models all women in the now due to the existence and the women equivalent in community life